Guarantee of Constitutional Rights for Legal Protection of Indonesian Migrant Workers in Brebes Regency - Khasanah, Karimatul; Wahyuningsih, Sri (Asian Journal of Law and Humanity, 2024)
Indonesian migrant workers (PMI) are an important part of contributing to the country's economic development. However, the constitutional rights of migrant workers are often neglected and adequate legal protection is often not met. Brebes Regency, as one of the areas that sends many migrant workers, requires strong guarantees to protect the constitutional rights of migrant workers. The research aims to determine the form of constitutional rights to legal protection in Brebes Regency and the Brebes Regency Government's efforts to provide constitutional rights in the form of legal protection to migrant workers. This research is empirical juridical research with a conceptual and statutory approach. The research results show that First ; There are four factors that cause why migrant workers have not maximally received their constitutional rights to legal protection in Brebes Regency, namely : There are no special regional regulations in Brebes Regency, there is no complete database of workers in Brebes Regency, lack of budget, there is no Unit Team. Duties (Task Force) in Brebes Regency. Second: There are various efforts made by the Brebes Regency Government to provide constitutional rights in the form of legal protection to migrant workers, such as: The Brebes Regency Government is trying as quickly as possible to create or ratify the latest Regional Regulations. Propose a budget to support legal protection. Immediately create a task force team to provide legal protection for Indonesian migrant workers in Brebes Regency, trying to improve services to increase legal protection in Brebes Regency.